A Study of Public University Libraries in Bangladesh in the Context of Collection Development through Open Access Resources - Islam, M. Monirul; Bhattacharya, Udayan (Journal of Information and Knowledge, 2023)
Libraries and librarians will benefit by acquiring a collection of open access information resources. The OA movement in Bangladesh is being developed to reduce the huge pressure on the library budget for subscriptions to journals. In most developed countries, university libraries view open-access materials as an important part of their collection development strategy. In this study, we examine the current state of OA resources in public university libraries in Bangladesh, collection development policies, the library authority's perspectives, the challenges libraries face in including OA resources in their collection development, and how to overcome those obstacles. Methodology: A survey and a stratified random sample technique were used in this study. A total of 276 students and 268 faculty members were surveyed. The first six public universities (in order of date of establishment) were selected. We sent out questionnaires directly to students, library personnel, librarians, and other library officials. Using library websites, journals, official records, and Google Scholar was another step. Findings: This study indicates that although open access materials may be quite useful in the growth of collections, most academic library authorities seem unconcerned about this. The utilization of open access materials in the overall collection is visible, but it is insignificant.